Using Accounting Information: A Simulation. - Beams, Floyd A.; Spiller, Earl A. (The Accounting Review, 1973)
Abstract The article reviews the book "Using Accounting Information: A Simulation," by Gary M. Cadenhead and Wayne A. Label.